PENGARUH TENUR AUDIT PERGANTIAN KAP DAN CLIENT IMPORTANCE TERHADAP KUALITAS AUDIT - Angela Oktavia (2022)
This study aims to empirically examine the effect of audit tenure, KAP Switching and client importance on audit quality by adding control variables for audit delay and leverage. The population used is manufacturing companies listed on the 2019-2020 BEI. Then the companies that were selected as samples through purposive sampling technique were 140 companies. In this study the method used is the quantitative method with secondary data. Then for the data analysis technique, namely logistic regression analysis with the help of STATA 14.2. From the results of the tests that have been carried out, it can be concluded that (1) the audit tenure have a significant effect on audit quality, (2) the KAP switching have no significant effect on audit quality, (3) client importance have a significant effect on audit quality, ( 4) control variables for audit delay and variabels for leverage have a significant effect on audit quality